LW jams in a mountain stream of Tierra del Fuego: piece movement and hydro-morphological effects analysis - Mao, Luca; Burns, Sarah; Comiti, Francesco; Andreoli, Andrea; Urciuolo, Adriana; Gaviño-Novillo, Marcelo; Iturraspe, Rodolfo; Aristide Lenzi, Mario (Bosque (Valdivia), 2008)
This work reports on the geomorphic role of large wood pieces and jams in a third order mountain stream located in Southern Tierra del Fuego (Argentina), and draining an old-growth nothofagus forested basin not influenced by beaver damming activity. Even if the in-stream number of wood pieces (2,300) is comparable to that observed in other climatic areas, the slow growth of the nothofagus forest causes a lower wood abundance in terms of volumetric load (121 m3 ha–1). Due to the relatively small dimensions of the large wood pieces located inside bankfull edges (83% of the total surveyed pieces), almost the 70% of them demonstrated to have been transported by runoff and 6% derived from bank erosion or landslides. Wood jams exert a significant influence on the channel morphology, being responsible for the creation of 30% of pools. The geomorphic influence of LW jams is also exerted by a considerable sediment storing capacity (about 1,750 m3). The LW-forced pool volume is strongly and positively correlated to the height of the LW jam. The results confirm that dead wood pieces, especially when organized in jams, play an important geomorphic role also in sub-Antarctic streams. The amount of large wood pieces quantified in the study site represents reference values for the assessment of the geomorphic effects of beaver activity in other Tierra del Fuego streams.